2007
DOI: 10.1007/s10682-006-9109-9
|View full text |Cite
|
Sign up to set email alerts
|

Flowering phenology of Ulex europaeus: ecological consequences of variation within and among populations

Abstract: Reproductive phenology of gorse (Ulex europaeus L., Genisteae, Fabaceae) is unusual in that the onset and duration of flowering vary greatly among individuals within populations: some plants initiate flowering in autumn or winter and continue flowering through spring, others initiate flowering in early spring. To understand the origin of this diversity and its ecological consequences, we investigated flowering phenology of randomly sampled individuals from five different natural populations in Brittany (France… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 54 publications
3
52
0
6
Order By: Relevance
“…Extended flowering duration might serve as a bet-hedging strategy to handle with tradeoffs both between pollinators and seed predators [37,56] and between pollinators and dispersers [53]. Interestingly, biotically pollinated plants flower for longer periods than do abiotically pollinated plants [20], as predicted if extended flowering evolves in response to tradeoffs between interactions with pollinators and other biotic agents.…”
Section: Multiple Interactions and Tradeoffsmentioning
confidence: 96%
See 2 more Smart Citations
“…Extended flowering duration might serve as a bet-hedging strategy to handle with tradeoffs both between pollinators and seed predators [37,56] and between pollinators and dispersers [53]. Interestingly, biotically pollinated plants flower for longer periods than do abiotically pollinated plants [20], as predicted if extended flowering evolves in response to tradeoffs between interactions with pollinators and other biotic agents.…”
Section: Multiple Interactions and Tradeoffsmentioning
confidence: 96%
“…Most field surveys compare temporal variation in the intensity of seed and flower predation and flowering phenology to infer the direction of selection acting on phenology. Most studies found that flowering off-peak (either early [23,[34][35][36][37], or late [11,[38][39][40][41]) is associated with reduced seed predation, probably because fewer herbivores are present at those times. Similar effects are highlighted by studies indicating highest seed predation during peak flowering [42][43][44], especially when peak flowering attracts more seed predators owing to a higher density of flowers and fruits ( [28], J.A.…”
Section: Interactions With Mutualists: Pollinatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the spring wildflower Mertensia fusiformis bet-hedges by delaying the opening of some flowers to ensure pollination and seed development in years with late spring frosts (Forrest & Thomson 2010). Similarly, the timing and duration of flowering in Ulex europaeus has been suggested to follow a bet-hedging strategy to spread out the risk of freezing, rotting, and seed predation (Tarayre et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…This system is particularly interesting because the relationship between U. europaeus and E. ulicis is very specific and very strong [19]. Indeed, the weevil undergoes its whole life-cycle on gorse, and gorse may suffer considerable damage from the weevils, which may infest up to 90% of the mature pods [19,20]. However, pod infestation rates are extremely variable in natural and experimental populations, and can vary from 20-98%, even among neighbouring individuals [19][20][21].…”
Section: Introductionmentioning
confidence: 99%